Impact of Didactic Strategies on Creative Pictorial Translation in Students of the I Cycle of Artistic Education of the School of Plastic Arts, Ayacucho, 2023 - Oriundo Mora, Katia (2023)
Through this quantitative, applied, explanatory research and quasi-experimental design, the researchers sought to analyze the impact of didactic strategies on improving creative pictorial translation in students of the I Cycle of the Professional Career of Artistic Education of the School of Plastic Arts of Ayacucho, 2023. From a population of 70 students from both professional majors, the researchers drew a census sample of 35 students for the control group (Professional Artist) and a similar number for the experimental group (Artistic Education). Furthermore, both the experimental plan and the checklist were the data collection instruments. By using relative frequency tables, the researchers presented the descriptive results. On the other hand, they analyzed the inferentials with Wilcoxon Rank and Whitney's U Mann. Thus, the results demonstrate that the control group does not suffer significant variation between the pre- and post-test; while the experimental group suffers significant variation, finding 23.6 points of difference between the assigned tests. Regarding the hypothesis test with Wilcoxon rank, the alternative hypothesis is accepted, concluding that the active teaching strategy allows improving creative pictorial translation in students of the experimental group investigated. In the same way, in the inference with Whitney's U Mann, the researchers find an essential difference between the control and experimental group in terms of creative pictorial translation. Therefore, the use of active teaching strategies is recommended to improve creative pictorial translation.